Differential coping capacities underlie the overall resistance of temperate seagrasses to herbivory - J. Boada; T. M. Smith; A. M. Ricart; T. Alcoverro; M. Pérez; J. Romero; N. Sanmartí; Y. Ontoria; M. Pierrejen; R. Arthur; D. Alonso; M. P. Adams; et al. (Ecosphere)
Abstract Grazing can impart long‐lasting changes in vegetated ecosystems. How ecosystems respond to herbivory depends on the ecological and evolutionary histories of their foundational species. The overall ecosystem functioning and associated biodiversity depend on these responses but there is still little understanding on how the intensity and duration of herbivory interact and impact vegetated ecosystems. We experimentally tested in the field the responses of three seagrass species with distinct life history traits to increasing intensities of herbivory over time. Specifically, we assessed structural responses (i.e., canopy height and shoot density) to reflect the ecosystem state. Additionally, we used mechanistic models to assess induced and constitutive responses in the different seagrass species. Results show that seagrasses coped with herbivory differentially in relation to their life history traits. Posidonia oceanica (persistent species) was resistant and only registered declines in canopy height, whereas both canopy heigh and shoot density rapidly decreased for Cymodocea nodosa (intermediate‐colonizing species) and Zostera noltei (colonizing species). Seagrasses also differed in the type of structural response, with the colonizing species experiencing reductions in shoot density, and the persistent P. oceanica registering declines in canopy height. After months of exposure to cumulative herbivory, all three species showed signs of stability. Interestingly, none of the species disappeared completely even when exposed to extreme herbivory. Mechanistic models indicate that herbivory‐induced responses are a potential explanation for these patterns. This study suggests that given the long evolutionary history of herbivory, some seagrasses may be remarkably well adapted to both intense and cumulative herbivory.